Inhibition Of In Vitro Growth Of Porcine Enterotoxigenic And Shiga Toxin-Producing Escherichia Coli By Lactobacillus Plantarum Strains - Park Changhoon (Sciendo, 2015)
The objective of this study was to assess cell-free fermented culture broth of 9 Lactobacillus plantarum strains as antibiotic alternatives for the inhibition of in vitro growth of enterotoxigenic Escherichia coli (ETEC) and Shiga toxin-producing E. coli (STEC) isolated from postweaning pigs with colibacillosis and edema disease in 2014. A total of 10 ETEC and 5 STEC strains isolated from postweaning pigs were tested in antimicrobial susceptibility tests. ETEC and STEC strains used in this study possessed at least one of fimbrial, enterotoxin, and Shiga-toxin genes when tested by polymerase chain reaction. Among 9 L. plantarum strains tested, 3 strains (Lp 2-05, 2-06, and 1-03) showed inhibitory activity of in vitro growth against 10 ETEC strains (100%) and 7 strains (Lp 6-13, 3-06, 3-05, 7-01, 2-06, 1-03, and 6-05) showed inhibitory activity of in vitro growth against 5 STEC strains (100%). Three strains (Lp 3-05, 2-06, and 1-03) showed inhibitory activity of in vitro growth against 10 ETEC (100%) and 5 STEC (100%) strains. The results of this study show the inhibitory activity of cell-free fermented culture broth of L. plantarum against ETEC and STEC isolated from postweaning pigs with colibacillosis and edema disease.